Broadband dual polarization patch element for cellular-phone base stations. - Yong-Xin Guo
A broadband dual polarization patch antenna double fed by an L-shaped probe and a near-resonant aperture is presented. The proposed antenna achieves a 1.5:1 standing wave ratio bandwidth of >20% at the two ports. Input isolation exceeding 25 dB has been obtained in the wide bandwidth. Thus, it can potentially be used as a base station antenna for cellular-phone networks
Keywords: 1.5 to 2.2 GHz; L-shaped probe; Broadband antenna; Cellular-phone base stations; Double antenna feed; Dual polarization antenna; Microstrip antennas; Near-resonant aperture; Patch antenna; Radiation patterns; Standing wave ratio bandwidth